Does Financial Distress Moderate the Effect of Leverage and Profitability on Going Concern Audit Opinions? - Heidy Paramitha Devi; Fatmawati, Ike Dian Nur; Sudrajat, Muhammad Agus; Wijaya, Anggita Langgeng (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2026)
Abstract Purpose – To empirically test the effect of profitability and leverage on going concern audit opinion and the ability of financial distress as a moderating variable is the purpose of this study. Methods – 160 samples were selected by purposive sampling method on mining sector companies listed on the Indonesia Stock Exchange in 2021−2024 mining company financial statements used as secondary data were analyzed by the logistic regression analysis method. Findings - The results of this study indicate that profitability does not affect going-concern audit opinion, while leverage does not affect going-concern audit opinion. The findings in this study also state that financial distress is unable to moderate the effect of profitability on going-concern audit opinion and financial distress is unable to moderate the effect of leverage on going-concern audit opinion. Implications - This research can be used as one of the considerations for users of financial statements and company management in making decisions. This study has several limitations on the independent variables of the study which are limited to only two financial ratios and limitations on the object of research so that it is not generalizable to other sector companies. Originality – The novelty of this research is the addition of moderating variables. Whereas in previous studies it is still rare to use financial distress as a moderating variable. In addition, updates are made in the year of research and the object under study.